DECISION SUPPORT SYSTEM OF PRODUCTION DEPARTMENT PROMOTION AT PT. RICHTEK GARMINDO WITH THE TOPSIS METHOD - Yehuda Prasetya Pramono; Dwi Setiawan (Lembaga Pengembangan Kinerja Dosen, 2021)
The development of information technology is currently very beneficial for the community, especially among government and private agencies. One of the advances in information technology that is often used by private agencies in solving structured or semi-structured problems is a Decision Support System (DSS). The Decision Support System is designed to support all stages of decision-making, starting from the stage of identifying problems, selecting relevant data, determining the approach used in the decision-making process to evaluating alternative selection activities. In addition, it is also used to support decisions such as making decisions about promotions. Promotion is a form of company appreciation for Human Resources for their work. Performance appraisals for promotions have also been widely carried out by private companies, one of which is in the field of garment manufacturing in the city of Semarang, PT. Richtek Garmindo is a private company engaged in garment Manufacturing. To get the Human Resources Assistant Chief Supervisior Sewing, the performance appraisal for promotion will be taken from the sewing section employees who are already competent in sewing. Currently, the promotion carried out by PT. Ricktek garmindo is not optimal and is still subjective because it still uses a manual system, namely each supervisor chooses or directly selects a sewing operator who is promoted with the criteria of work skills only, the selection made by the supervisor is also still using kinship values in the selection process, and because there are too many sewing operators and the absence of an integrated system, the selection process still takes approximately 1 month to get sewing operators who are ready to be promoted.